Separation of close isomers by enclathration - Horne, Alicia (Department of Chemistry, 2016)
The selective inclusion properties of the host compound 1, 1-bis-( 4- hydroxyphenyl)cyclohexane were investigated. This host readily forms inclusion compounds with the isomers of phenylenediamine, benzenediol, picoline and lutidine, as well as selected solvents including methanol, ethanol, i-propanol, n-butanol, ethyl acetate and dioxane. The crystal structures of the complexes formed were elucidated, and comparisons were made between the packing of the complexes, and the intermolecular interactions between the host and guest components of the complexes. The complexes were characterised using thermal analysis and X-ray powder diffraction. The lattice energies of the complexes were calculated to determine their relative stability. The kinetics of desolvation of the picoline and lutidine inclusion compounds were studied, using isothermal and non-isothermal thermogravimetry. These experiments yielded the kinetic models as well as the activation energies of the desolvation reactions. Competition experiments were performed to determine which isomers of the compounds mentioned above were enclathrated preferentially by the host, and the observed selectivity was related to differences in complementary between the host and guest components in each complex. Inclusion compounds were formed between the host and the solid guests (benzenediol and phenylenediamine) by means of solid-solid reactions. The complexes were formed by grinding the two powdered starting components together in a ball mill. The resulting products were analysed by X-ray powder diffractometry. Competition experiments were also performed in the solid state to determine whether the selectivity of the host differed from that observed in solution.